2011
DOI: 10.1007/s10765-011-1067-y
|View full text |Cite
|
Sign up to set email alerts
|

Combined FPPE–PTR Calorimetry Involving TWRC Technique II. Experimental: Application to Thermal Effusivity Measurements of Solids

Abstract: Photopyroelectric calorimetry in the front detection configuration (FPPE) and photothermal radiometry (PTR) were simultaneously used, together with the thermal-wave resonator cavity method (TWRC), in order to investigate the thermal effusivity of solids inserted as backing layers in a detection cell. A new combined FPPE-PTR-TWRC setup was designed. It was demonstrated experimentally that the PTR technique, combined with the TWRC method, is able to provide calorimetric information about the third layer of a det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Even though the term A f contains the effusivity of the sample and the substrate, it remains undetectable and just acts as an offset for the amplitude. We have done simulations for the full model, equation (5), and the reduced model, equation (7), and found that the reduced model is quite valid in our experimental range of frequencies. Equation ( 7) is particularly useful due to its rather direct and only exponential term to find the sample's thermal diffusivity evolution as a function of time, temperature or electric field.…”
Section: Back-front Ptrmentioning
confidence: 88%
See 2 more Smart Citations
“…Even though the term A f contains the effusivity of the sample and the substrate, it remains undetectable and just acts as an offset for the amplitude. We have done simulations for the full model, equation (5), and the reduced model, equation (7), and found that the reduced model is quite valid in our experimental range of frequencies. Equation ( 7) is particularly useful due to its rather direct and only exponential term to find the sample's thermal diffusivity evolution as a function of time, temperature or electric field.…”
Section: Back-front Ptrmentioning
confidence: 88%
“…In this paper, we propose the PTR technique as an alternative calorimetry. Concerning the accuracy of the investigations, in both techniques, when using sandwiched detection cells, it was demonstrated [23,5] that it is connected with the values of the thermal parameters of the layers of the detection cell; more exactly, the accuracy is increased when the values of the thermal effusivity of the liquid and backing layers are close. In the PTR configurations proposed in this paper, the backing layer is glass with a thermal effusivity rather close to the typical liquids, so the experiment is optimized in order to obtain high accuracy.…”
Section: B-ptr Experiments On 5cb With Varying Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…A few years ago, new methods were reported for the direct and simultaneous estimation of κ and C. One was a modified photopyroelectric (PPE) method 5,6) and the other was the combination of PPE and photothermal reflectance (PTR) methods. 7,8) The original PPE method [9][10][11][12][13] is a relatively simple and sensitive measurement technique for the thermal diffusivity α. In the PPE method, it is necessary to attach a temperature sensor to the sample.…”
Section: Introductionmentioning
confidence: 99%